Cadmium-free low-silver solder

CN119407400AActive Publication Date: 2025-02-11NANJING UNIV OF SCI & TECH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411715459.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-11
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

[0007]但是,由于上述无镉低银钎料均添加了较高含量的In、Ga元素,除了成本偏高因素外,还因为In、Ga属于“稀有金属”,无论是地球上的储量还是全世界的年产量均很少,不适合大量使用

Benefits of technology

[0008] The object of the present invention is to provide a cadmium-free low-silver solder material. The Ag content in the silver solder material is in the range of 6.0% to 8.0%, and the liquid phase line temperature is ≤750°C. It is suitable for copper-brass, copper-stainless steel, and yellow Brazing of copper-stainless steel and other materials can meet the needs of brazing users to reduce costs, improve product quality, and enhance product market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156786040000061
    Figure BDA0005156786040000061
Patent Text Reader

Abstract

The invention discloses a cadmium-free low-silver brazing filler metal. The brazing filler metal is prepared from the following components in percentage by mass: 6.0 percent to 8.0 percent of Ag, 39.0 percent to 43.0 percent of Zn, 13.0 percent to 14.5 percent of Sn, 0.05 percent to 0.1 percent of In, 0.05 percent to 0.1 percent of Ga, 2.5 percent to 3.5 percent of Ni, 0.005 percent to 0.01 percent of Be, 0.0001 percent to 0.0005 percent of nano cadmium telluride and the balance of Cu. The solidus temperature of the brazing filler metal is smaller than or equal to 680 DEG C, and the liquidus temperature is smaller than or equal to 745 DEG C. When the brazing filler metal is matched with commercially available FB102 brazing flux to braze red copper-Q235 steel, red copper-brass and brass-stainless steel, the shearing strength of a brazed joint is superior to that of existing BAg12CuZn (Si) brazing filler metal and BAg5CuZn (Si) brazing filler metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brazing materials of metal materials, and in particular relates to a cadmium-free and low-silver brazing filler metal. Background Art

[0002] The BAg20CuZn(Si) solder recommended in existing literature such as GB / T 10046-2018 "Silver Solder" has a melting temperature range of 690℃ solidus and 810℃ liquidus, and is one of the most popular and cost-effective silver solders on the market. However, with its 20%±1% Ag content, the price of precious metal silver continues to rise, silver solder users face fierce competition, and require continuous reduction of material costs to improve product competitiveness. The development of cadmium-free low-silver silver solders with lower silver content and better performance has always been a hot topic for technicians in the relevant manufacturing industry.

[0003] The study found that the melting temperature range of BAg5CuZn(Si) solder with low silver content in GB / T 10046-2018 "Silver solder" is 820℃ solidus and 870℃ liquidus; the melting temperature range of BAg12CuZn(Si) solder is 800℃ solidus and 830℃ liquidus. The above two low-silver solders provide users with a cost-reducing option, but the solidus and liquidus temperatures of the solders are both higher than 800℃, which can easily cause "overburning" and "softening" of copper and copper alloys, and are therefore not conducive to the brazing of copper and copper alloy structures.

[0004] The inventors found through literature search that in the published Chinese patent documents, the technical information about the new low-silver solder is briefly listed. For example, document CN 115533365A reports a cadmium-free low-silver solder, which is composed of 8.0% to 10.0% Ag, 38.0% to 42.0% Zn, 6.0% to 10.0% Sn, 1.5% to 2.5% In, 1.5% to 2.5% Ga, 1.5% to 2.5% Ni, 0.0001% to 0.0005% nano-HfC, 0.0001% to 0.0005% nano-ZrC and the balance is Cu. The solidus temperature of the solder is ≤700°C and the liquidus temperature is ≤750°C. Document CN 116871736A reports a cadmium-free low-silver solder and a preparation method thereof, wherein the cadmium-free low-silver solder is composed of 4.0% to 5.0% Ag, 40.0% to 45.0% Zn, 11.0% to 13.0% Sn, 0.5% to 1.5% In, 0.5% to 1.5% Ga, 0.5% to 1.5% Ni, 0.01% to 0.05% nano CeO2, 0.01% to 0.05% nano Y2O3 and the balance is Cu, and the solder has a solidus temperature of ≤735°C and a liquidus temperature of ≤780°C. The Ag content of the above two low-silver solders is less than or equal to 10%, but both are added with relatively high content of In and Ga elements, and the cost is still high.

[0005] A large number of studies have pointed out that the common feature of reducing the melting temperature (such as solidus temperature and liquidus temperature) of cadmium-free silver solder is to add at least one or more low-melting-point elements such as Sn (melting point 231.9℃), In (melting point 156.6℃), Ga (melting point 29.76℃), Li (melting point 180.5℃) and alloying elements Ni that can reduce the melting point of solder. Since In, Ga and Li are "rare elements", the annual production in the world is also very limited, and the price of In and Ga is equivalent to or higher than that of silver; due to the rapid development of new energy vehicles, the price of Li has also risen wildly to 3 million yuan / ton (3,000 yuan / kg) in recent years, which is much higher than Cu (about 80 yuan / kg). Therefore, when the addition amount of In and Ga is higher than 1.5wt.%, the value of mass production application will be greatly reduced; the price of Sn element is not high compared to Ag and the reserves are relatively abundant, but when Sn is added in large quantities, it is easy to form hard and brittle intermetallic compounds Cu6Sn5, which makes the silver solder "difficult to process". According to literature reports, except for the BAg60CuSn solder in which the Sn addition can reach 9.5% to 10.5%, the Sn addition in the Ag-Cu-Zn-Sn series solders is generally 1.5% to 2.5%. Only in some individual models such as BAg56CuZnSn, the Sn addition is 4.5% to 5.5% (see GB / T10046-2018 "Silver Solder", page 4, Table 1 (continued)).

[0006] Although document CN 115533365A reports that the Sn addition amount can be as high as 10.0%, and the solidus temperature of the obtained cadmium-free low-silver solder is ≤700°C, and the liquidus temperature is ≤750°C; document CN 116871736A reports that the Sn addition amount can be as high as 11.0% to 13.0%, and its solidus temperature is ≤735°C, and its liquidus temperature is ≤780°C, which is close to or even better than the melting temperature of BAg20CuZn(Si) solder, and basically meets the brazing requirements of copper and copper alloy structures.

[0007] However, since the above-mentioned cadmium-free and low-silver solders all contain relatively high levels of In and Ga elements, in addition to the high cost factor, In and Ga are "rare metals" and are not suitable for large-scale use, both in terms of their reserves on the earth and their annual production worldwide. Therefore, how to use the abundant Sn element to replace In and Ga, and how to add In and Ga elements as "trace elements" to achieve the purpose of lowering the melting temperature of the new solder and improving the solder joint strength still requires a lot of exploration and research. Summary of the invention

[0008] The purpose of the present invention is to provide a cadmium-free low-silver solder, in which the Ag content is in the range of 6.0% to 8.0%, the liquidus temperature is ≤750°C, and the solder is suitable for brazing materials such as copper-brass, copper-stainless steel, and brass-stainless steel, thereby meeting the needs of solder users to reduce costs, improve product quality, and enhance product market competitiveness.

[0009] The technical solution for achieving the purpose of the present invention is as follows:

[0010] The invention discloses a cadmium-free low-silver solder, which comprises, by mass percentage, 6.0% to 8.0% of Ag, 39.0% to 43.0% of Zn, 13.0% to 14.5% of Sn, 0.05% to 0.1% of In, 0.05% to 0.1% of Ga, 2.5% to 3.5% of Ni, 0.005% to 0.01% of Be, 0.0001% to 0.0005% of nano-cadmium telluride (CdTe), and the balance of Cu.

[0011] Furthermore, the particle size of the nano-cadmium telluride is 100nm-150nm.

[0012] The cadmium-free low-silver solder of the present invention uses silver plate, cathode copper, zinc ingot, tin ingot, metal indium, metal gallium and metal nickel added in a proportion of components, and smelted by medium frequency smelting process. Before casting, a trace amount of nano CdTe and Be-Cu powder is coated with copper foil, put into a graphite "bell jar" and quickly inserted into the molten solder liquid, stirred evenly and cast into an ingot. Then, the required solder wire is obtained by extrusion and drawing.

[0013] The solidus temperature of the solder of the present invention is ≤680°C, and the liquidus temperature is ≤745°C. When the solder is used with the commercially available FB102 solder, the shear strength of the soldered joint is better than that of the existing BAg12CuZn(Si) solder and BAg5CuZn(Si) solder when brazing red copper-Q235 steel, red copper-brass, and brass-stainless steel.

[0014] By comparing and analyzing the current valid version of the EU RoHS2.0 directive and the current valid version of the GB / T 10046-2018 "Silver Solder" standard, it is found that the cadmium content in the silver solder is required to be no more than 0.010% (i.e., Cd≤0.010%). The solder of the present invention only adds 0.0001% to 0.0005% nano-cadmium telluride (CdTe), which is equivalent to a maximum amount of Cd element of only 0.000234%, which fully meets the requirements of the RoHS2.0 directive and the GB / T 10046-2018 standard. DETAILED DESCRIPTION

[0015] Compared with previous studies, the technical solution of the present invention creatively solves the following key technical problems:

[0016] (1) It was found that adding a small amount of nano-cadmium telluride (particle size of 100nm-150nm) to a cadmium-free low-silver solder with a silver content of 6.0%-8.0% can significantly refine the Cu6Sn5 grains and significantly inhibit the formation of Cu6Sn5. At the same time, appropriately increasing the Ni content to 2.5%-3.5% can significantly transform the brittle and hard Cu6Sn5 into a (Cu,Ni)6Sn5 intermetallic compound with good plasticity, so that the solder of the present invention can still be smoothly processed into wire even when the Sn content is as high as 13.0%-14.5%.

[0017] Although the document CN 115533366A reports that adding trace rare earth metal Sm, metal Yb elements and trace nano Sm2O3 and nano Yb2O3 oxides to high tin copper-phosphorus solder can significantly refine the grains of the copper-phosphorus solder, especially the grains of the intermetallic compounds Cu6Sn5 and (Cu,Ni)6Sn5, the maximum particle size of the intermetallic compound (i.e. (Cu,Ni)6Sn5) can only reach ≤5μm, and the amount of Sn added to the solder can only reach 8.0% to 11.0%. The present invention adopts the technical solution of adding CdTe, which can refine the maximum particle size of Cu6Sn5 and (Cu,Ni)6Sn5 to ≤3μm, so that the solder of the present invention can still be smoothly processed into wire even when the Sn content is as high as 13.0% to 14.5%, which is not achieved in the prior art and has not been reported. In addition, the addition of 13.0% to 14.5% Sn content also makes the melting temperature range of the cadmium-free low-silver solder of the present invention significantly lower than the solidus line 820°C and liquidus line 870°C of the BAg5CuZn(Si) solder to the solidus line ≤680°C and liquidus line ≤745°C, which fully meets the brazing requirements of copper-containing and copper alloy structures.

[0018] (2) It was found that by adding a trace amount of Be on the basis of adding a trace amount of 0.0001% to 0.0005% nano-cadmium telluride (CdTe), and utilizing the "synergistic effect" of Te and Be elements, the cadmium-free and low-silver solder of the present invention has excellent plasticity. Therefore, the solder of the present invention is easy to process, and there is no need to adjust the original equipment and process during extrusion and drawing.

[0019] The invention optimizes the addition amounts of main component elements, trace alloy elements, nano-CdTe and Be elements, and determines that the addition amounts of In and Ga elements are respectively 0.05% to 0.1%, and the addition amount of Be element is controlled in the best range of 0.005% to 0.01%.

[0020] The test found that compared with BAg12CuZn(Si) and BAg5CuZn(Si) solders, the solder spreading area on copper, H58 brass, Q235 steel and 304 stainless steel was significantly improved by more than 10%; the tensile strength of the solder joint (σ b ) and shear strength (τ) were increased by more than 20% to 30%, reaching and exceeding the levels of BAg12CuZn(Si) and BAg5CuZn(Si) solders, see Table 1.

[0021] The nano-cadmium telluride of the present invention can be made from commercially available products or can be synthesized into nano-powder by chemical reduction. The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0022] Example 1

[0023] A cadmium-free low-silver solder comprises, by mass percentage, 6.0% of Ag, 43.0% of Zn, 13.0% of Sn, 0.1% of In, 0.05% of Ga, 3.5% of Ni, 0.005% of Be, 0.0001% of nano CdTe, and the remainder is Cu.

[0024] The cadmium-free low-silver solder obtained by using the above composition ratio has a solidus temperature of ≤680℃ and a liquidus temperature of ≤745℃ (both considering the measurement error). It has excellent wetting and spreading properties on copper, H58 brass, Q235 steel, and 304 stainless steel. When using flame brazing with FB102 brazing flux, the brazing seam strength when the brazing base materials are the following combinations is shown in the brackets: copper-H58 brass (σ b =260±10MPa, τ=255±10MPa), copper-Q235 steel (σ b =350±10MPa, τ=350±10MPa), H58 brass-304 stainless steel (σ b =360±10MPa, τ=355±10MPa). The brazing joint strength of the new solder is significantly higher than that of the BAg12CuZn(Si) solder and the BAg5CuZn(Si) solder under the same conditions.

[0025] Example 2

[0026] A cadmium-free low-silver solder comprises, by mass percentage, 8.0% of Ag, 39.0% of Zn, 14.5% of Sn, 0.05% of In, 0.1% of Ga, 2.5% of Ni, 0.01% of Be, 0.0005% of nano CdTe, and the remainder is Cu.

[0027] The cadmium-free low-silver solder obtained by using the above composition ratio has a solidus temperature of ≤680℃ and a liquidus temperature of ≤745℃ (both considering the measurement error). It has excellent wetting and spreading properties on copper, H58 brass, Q235 steel, and 304 stainless steel. When using flame brazing with FB102 brazing flux, the brazing seam strength when the brazing base materials are the following combinations is shown in the brackets: copper-H58 brass (σ b =260±10MPa, τ=255±10MPa), copper-Q235 steel (σ b =350±10MPa, τ=350±10MPa), H58 brass-304 stainless steel (σ b =360±10MPa, τ=355±10MPa). The brazing joint strength of the new solder is significantly higher than that of the BAg12CuZn(Si) solder and the BAg5CuZn(Si) solder under the same conditions.

[0028] Example 3

[0029] A cadmium-free low-silver solder comprises, by mass percentage, 7.0% of Ag, 41.0% of Zn, 14.0% of Sn, 0.08% of In, 0.07% of Ga, 3.0% of Ni, 0.008% of Be, 0.0003% of nano CdTe, and the balance is Cu.

[0030] The cadmium-free low-silver solder obtained by using the above composition ratio has a solidus temperature of ≤680℃ and a liquidus temperature of ≤745℃ (both considering the measurement error). It has excellent wetting and spreading properties on copper, H58 brass, Q235 steel, and 304 stainless steel. When using flame brazing with FB102 brazing flux, the brazing seam strength when the brazing base materials are the following combinations is shown in the brackets: copper-H58 brass (σ b =260±10MPa, τ=255±10MPa), copper-Q235 steel (σ b =350±10MPa, τ=350±10MPa), H58 brass-304 stainless steel (σ b =360±10MPa, τ=355±10MPa). The brazing joint strength of the new solder is significantly higher than that of the BAg12CuZn(Si) solder and the BAg5CuZn(Si) solder under the same conditions.

[0031] Comparative Example 1

[0032] A cadmium-free low-silver solder comprises, by mass percentage, 7.0% of Ag, 41.0% of Zn, 14.0% of Sn, 0.08% of In, 0.07% of Ga, 3.0% of Ni, 0.008% of Be, and the balance is Cu.

[0033] The cadmium-free low-silver solder obtained by the above-mentioned composition ratio has no change in the solidus temperature and liquidus temperature of the solder (such as solidus temperature ≤ 680°C, liquidus temperature ≤ 745°C (both considering the measurement error)), but the processing performance is significantly reduced. The wetting and spreading performance on copper, H58 brass, Q235 steel, and 304 stainless steel is also significantly worse than that in the embodiment. When using flame brazing with FB102 brazing flux, the brazing seam strength of the following combinations of brazing base materials is reduced. See the data in brackets: copper-H58 brass (σ b =250±10MPa, τ=245±10MPa), copper-Q235 steel (σ b =340±10MPa, τ=335±10MPa), H58 brass-304 stainless steel (σ b =345±10MPa, τ=335±10MPa).

[0034] Although the brazing joint strength of the comparative example 1 solder is higher than the brazing joint strength of the BAg12CuZn(Si) solder and the BAg5CuZn(Si) solder obtained under the same conditions, it is significantly lower than that of Examples 1, 2 and 3.

[0035] Comparative Example 2

[0036] A cadmium-free low-silver solder comprises, by mass percentage, 7.0% of Ag, 41.0% of Zn, 14.0% of Sn, 0.08% of In, 0.07% of Ga, 3.0% of Ni, 0.0003% of nano CdTe, and the remainder is Cu.

[0037] The cadmium-free low-silver solder obtained by the above composition ratio has a solidus temperature of ≤680℃ and a liquidus temperature of ≤745℃ (both considering the measurement error), but the processing performance is significantly reduced. The wetting and spreading performance on copper, H58 brass, Q235 steel, and 304 stainless steel is also significantly worse than that of the embodiment. When using flame brazing with FB102 brazing flux, the brazing seam strength of the following combinations of brazing base materials is reduced. See the data in brackets: copper-H58 brass (σ b =250±10MPa, τ=245±10MPa), copper-Q235 steel (σ b =340±10MPa, τ=335±10MPa), H58 brass-304 stainless steel (σ b =345±10MPa, τ=335±10MPa).

[0038] Although the brazing joint strength of the comparative example 2 solder is higher than the brazing joint strength of the BAg12CuZn(Si) solder and the BAg5CuZn(Si) solder obtained under the same conditions, it is significantly lower than that of Examples 1, 2 and 3.

[0039] Table 1 shows the solder spreading performance (spreading area, mm2) of Examples 1 to 3 and commercially available BAg5CuZn(Si) solder and commercially available BAg12CuZn(Si) solder. 2 ) and brazing joint strength. From the data of comparative examples 1 and 2, it can be seen that when metal Be or nano-CdTe is added alone, the wetting and spreading performance of the solder will deteriorate, and the mechanical properties of the solder joint will also decrease significantly, which fully demonstrates the significant influence of the "synergistic effect" of metal Be and nano-CdTe on the spreading performance of the solder and the strength of the solder joint.

[0040] Table 1

[0041]

Claims

1. A cadmium-free low-silver solder, characterized in that: The proportions by mass percentage are: 6.0% to 8.0% Ag, 39.0% to 43.0% Zn, 13.0% to 14.5% Sn, 0.05% to 0.1% In, 0.05% to 0.1% Ga, 2.5% to 3.5% Ni, 0.005% to 0.01% Be, 0.0001% to 0.0005% nano-cadmium telluride, and the balance is Cu.

2. The cadmium-free low-silver solder according to claim 1, characterized in that: The particle size of nano-cadmium telluride is 100nm to 150nm.

Citation Information

Patent Citations

  • High-tin rare earth copper phosphorus brazing filler metal and preparation method thereof

    CN115533366A

  • Cadmium-free low-silver solder

    CN116871736A

  • Beryllium-containing low-silver cadmium-free silver solder

    CN103817456A

  • Low-cadmium silver solder

    CN106736021A

  • Low-melting-point low-cadmium silver solder containing rare earth elements

    CN106736022A